Kaidah-Kaidah Penafsiran Tentang Pedoman Dalam Kehidupan Bagi Masyarakat - Kurniadi Ramadhan; Pathur Rahman; Muhamad Nasrullah (Yayasan Cendekia Gagayunan Indonesia, 2024)
This article discusses the interpretive principles regarding life guidelines that are relevant in the context of daily life, with the aim of exploring moral principles that can be implemented to achieve the well-being of individuals and society. The method used is qualitative analysis by reviewing literature and concrete examples of the application of these principles. The results indicate that the application of principles such as disregarding what is harmful, concentrating on work, hastening to do good, and striving for the common good according to one's ability can enhance the quality of life and individual success, as well as provide positive impacts for society. This research offers recommendations for applying these principles in daily life to achieve common goals. If you need any further assistance or adjustments, feel free to let me know